Marketing Mix Strategies and Challenges in Increasing the Income of Palm Sugar Artisans in Lombo Village, Pitu Riase District, Sidenreng Rappang Regency - Liska Lina Yanti; Adam Latif; Andi Riska Andreani Syafaruddin; H. Haslindah (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study examines the implementation of the marketing mix strategy (4P: product, price, place, and promotion) as an effort to increase the income of palm sugar artisans in Lombo Village, Pitu Riase District, Sidenreng Rappang Regency, South Sulawesi. Despite the significant potential of the local agribusiness sector, palm sugar artisans continue to face several challenges, including the remote location of plantations, the susceptibility of palm sap to fermentation, dependence on intermediaries, and the use of traditional word-of-mouth marketing practices. Therefore, this study aims to analyze existing market conditions and identify sustainable marketing mix strategies that can support increased sales and income among palm sugar artisans. This research employed a qualitative approach. Data were collected through observations, documentation, literature reviews, and interviews. The study involved 10 informants, consisting of 3 business owners and 7 customers. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing. The data were processed using NVivo 12 Pro software. The findings indicate that product quality is the most influential factor affecting customer satisfaction and repeat purchases, while promotion remains the weakest element due to the limited utilization of digital marketing and the continued reliance on traditional word-of-mouth communication. Based on these findings, the study recommends maximizing the use of social media as a promotional platform, investing in supporting production equipment, and maintaining consistency in the palm sugar production process to enhance competitiveness and increase artisans' income.